Training the future translators for professional activities in the modern informational space (Pedagogy of Higher and Secondary Education, 2014)
Tarasenko R. А.Training the future translators for professional activities in the modern informational space.The article deals with problems of the activities of the future translators in today’s informational space. A formative influence of its components on information competencies in the training of translators in accordance with the current requirements of the informational society are considered.
Keywords: informational society; informational space; Internet resources; database; information technology; translator